Update on Robotic Laparoscopic Radical Prostatectomy - Garrett S. Matsunaga; Thomas E. Ahlering; Douglas W. Skarecky (The Scientific World Journal)
The da Vinci surgical robot has been shown to help shorten the learning curve for laparoscopic radical prostatectomy (LRP) for both laparoscopically skilled and na surgeons[1,2]. This approach has shown equal or superior outcomes to conventional laparoscopic prostatectomy with regard to ease of learning, initial complication rates, conversion to open, blood loss, complications, continence, potency, and margin rates. Although the data are immature to compare oncologic and functional outcomes to open prostatectomy, preliminary data are promising.Herein, we review the technique and outcomes of robotic-assisted laparoscopic radical prostatectomy (RALP).